COMMERCIAL BANK BEHAVIOR AND THE LEVEL OF ECONOMIC ACTIVITY: AN ECONOMETRIC STUDY* - Goldfeld, Stephen M. (Journal of Finance, 1965)
Thesis (Ph. D.)–Massachusetts Institute of Technology, Dept. of Economics and Social Science, 1963.